PROSES SINTERING PADA KERNEL URANIUM DIOKSIDA (UO2) - , Fitrotun Aliyah; , Prof. Ir. Wahyudi Budi Sediawan, SU., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
UO2 kernel sintering process is one of parts of the preparation of nuclear fuel elements for High Temperature Reactor. Sintering process is the final stage in the manufacture of the fuel kernel prior to coating process. This stage is very important in the whole process because it will determine the feasibility of UO2 kernel according to the High Temperature Reactor fuel specifications. This research was conducted by preparing the raw materials sample, heating sample to high temperatures in argon gas atmosphere, and analyzing the kernel from sintering process. Kernel diameter analysis was conducted by the Dinolite capture, density analysis was conducted by Pycnometer, specific surface area and total pore volume analysis was conducted by NOVA-1000. Mathematic models used were Model I (Single Reaction), Model II (Series Reactions with ks and kp following Arrhenius equation) and Model III (Series Reactions with ks and kp following modified Arrhenius equation). The aims of this research are: to get UO2 kernel with a high density which is â¥ 95% TD, to develope mathematic model of the sintering process and to obtain the value of the parameters sintering i.e. As, Es, Ap, Ep, and ÏC. It turned out that the highest density is 92.56% TD or approximately 10.1441 g/cm3 that was at the sintering temperature of 1400 Â° C within 2 hours. The diameter is about 919Î¼m, specific surface area is 4.4213 m2/g, and total pore volume is 4.7515x10-3 cm3/g. Model III (Series Reactions with ks and kp following modified Arrhenius equation) is the best fit of Mathematic models with the value of average error is 1.02%. Sintering parameters resulted from curve fitting with Model III are the activation energy of sintering (Es) of 24 kJ/mol, the activation energy of destruction (Ep) of 16 kJ/mol, and the density of the kernel C (ÏC) of 8.34 g/cm3. Meanwhile the value of the collision frequency of sintering (As) and the collision frequency of destruction (Ap) depend on the temperature by the equation of: ð´ð =1.8188 x 10â2ð and ð´ð=4.9753 x 106 ðâ2.